Drag augmentation systems for space debris mitigation - Serfontein, Zaria; Kingston, Jennifer; Hobbs, Stephen; Holbrough, Ian E.; Beck, James C. (International Astronautical Federation (IAF), 2020)
Space debris is recognised as a critical threat for the space industry. The proliferation of small satellites has invited commercialisation and subsequently, the growing number of satellites are adding to the already high number of objects currently in low-Earth orbit (LEO). Low-cost small satellites are under increasing pressure to meet debris mitigation guidelines and failure to comply could result in a launch licence being denied. Drag augmentation systems increase the drag area of a spacecraft, minimising the de-orbit period and thus reducing the probability of significant collisions and supporting the sustainable use of space. In response to the growing number of small satellites (10-500 kg) unable to de-orbit from low-Earth orbit within 25 years, Cranfield University has developed a family of drag augmentation systems (DAS). The DAS are lightweight, cost-effective sails deployed at end of mission and are reliable solutions for deorbiting small satellites, assisting in the conservation of the space environment. Three drag sails designed, manufactured and tested at Cranfield University are currently in orbit, with two sails already successfully deployed. This paper details the sails and will discuss findings from recent studies; examining the system’s scalability, the post-deployment vehicle dynamics, the medium-term impact of the sail on the satellite’s ability to conduct science and the long-term effect of the sail on the satellite’s re-entry and demise. The DAS technology have a strong enabling potential for future space activities, allowing satellites to operate responsibly and sustainably.
Keywords: Space Debris; Drag Sails; De-Orbit Systems; Sustainable Space; Small Satellites; Low Earth Orbit